'The King's Irishmen': the roles, impact and experiences of the Irish in the exiled court of Charles II, 1649-1660 - Williams, M; Mark R F Williams (2010)
This thesis represents an important investigation into the much-neglected period of exile endured by many Royalists as a consequence of the violence and alienation of the Wars of the Three Kingdoms (1639-1651).Drawing from extensive archival research conducted in Britain, Ireland and Europe, this study expands upon existing literature on royalism, British and Irish interaction with Continental Europe and seventeenth-century mentalities more generally in order to illumine the unique issues faced by these exiles. Central to this study are the roles and experiences of the Irish element within Charles II’s exiled court. Recent studies focussed upon the place of Ireland within Europe and the North Atlantic are employed to assess such issues as confessional division, court culture, the impact of memory and the influence of conflicting European ideas upon the survival of the exiles and the course of the restoration cause. A thematic, rather than chronological structure is employed in order to develop these interpretations, allowing for an approach which emphasizes the place of individuals in relation to broader Royalist mentalities. Dominant figures include Murrough O’Brien, Lord Inchiquin (c. 1614-1674), Theobald, Lord Taaffe (d. 1677), John Bramhall (1594-1663), Church of Ireland bishop of Derry, Daniel O’Neill (c. 1612-1664), Father Peter Talbot (SJ) (c. 1618/20 – 1680) and James Butler, marquis of Ormond (1610-1688). Through investigation of Irish strands of royalism and the wider issues in which they were set in the course of civil war and exile, this thesis makes a powerful argument for the need to consider seventeenth-century ideas of allegiance and identity not only within a ‘Three Kingdoms’ approach, but Europe more generally. It also makes a compelling case for the centrality of Irish Royalists in the formation and implementation of policy during the exile period through their familiarity with and access to European centres of power and influence.